Defining the Relevance of Signs and Symptoms to Identify Exit Site Infection of a Hemodialysis Central Venous Catheter: A Delphi Study Protocol - José Luis Cobo-Sánchez; Joan Ernest de Pedro-Gómez; Noelia Mancebo-Salas; Raquel Pelayo-Alonso; Ian Blanco-Mavillard (International Journal of Qualitative Methods, 2021)
Vascular access is a potentially fatal vulnerability for hemodialysis patients, and a notable area for improvement for healthcare providers. Hemodialysis central venous catheters (HD-CVC) are associated with increased morbidity and mortality from infectious complications. Clinical practice guidelines on vascular access for hemodialysis and infection control do not provide a standard definition for infection of the HD-CVC exit site. The main aim of this protocol is to establish consensus on the signs and symptoms for preventing CVC exit site infection for patients receiving hemodialysis, based on the opinion of a panel of experts. The secondary study aim is to determine the optimum treatment approach according to the signs and symptoms of infection at the HD-CVC exit site, as prioritized by the panel of experts. For this purpose, a modified ranking-type Delphi technique will be used, with three rounds of evaluation conducted via an online questionnaire: the first two rounds will be used to prioritize, by consensus, the most relevant signs and/or symptoms of infection of the HD-CVC exit site or tunnel. Once this consensus has been achieved, a third round of evaluation will be conducted, asking the participants to ascertain the most appropriate treatment approach. The research team has drawn up a list of signs and symptoms related to infection of the HD-CVC exit site or tunnel, based on the definitions obtained from a previous systematic review. The results of the present study will enable us to design an assessment scale for HD-CVC exit sites, thus facilitating early identification and action if infection occurs. The availability of such an instrument will benefit not only clinical practice, but also research, healthcare education and training programs for professionals in this area.